1999
DOI: 10.1051/apido:19990208
|View full text |Cite
|
Sign up to set email alerts
|

Selecting honey bees for resistance to Varroa jacobsoni

Abstract: -This report describes a systematic approach to selecting honey bees (Apis mellifera L.) for resistance to Varroa jacobsoni Oudemans. The equation (P 1 (ab) n = P 2 ) describes the growth of the mite population in a colony of honey bees that has a constant supply of worker brood. P 1 and P, are the initial and final mite populations, a is population change while mites are in brood cells, b is population change outside brood cells and n is the number of reproductive cycles of the mite. By comparing the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 12 publications
(15 reference statements)
2
79
2
3
Order By: Relevance
“…Many researchers reported that the level of hygienic behaviour showed variability depending on the subspecies of honey bee and colonies in the same apiary (1,3,6,11,28). For that reason, this behaviour has to be evaluated as a skill arising from genetic differences (2,14,29). On the other hand, in our study during the 5 months, the experimental colonies experienced many internal and external factors, including brood rearing, changes in adult worker bee population, building of combs, nectar and pollen collection, harvesting of honey, parasites, and predators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers reported that the level of hygienic behaviour showed variability depending on the subspecies of honey bee and colonies in the same apiary (1,3,6,11,28). For that reason, this behaviour has to be evaluated as a skill arising from genetic differences (2,14,29). On the other hand, in our study during the 5 months, the experimental colonies experienced many internal and external factors, including brood rearing, changes in adult worker bee population, building of combs, nectar and pollen collection, harvesting of honey, parasites, and predators.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is accepted that hygienic behaviour is the basic mechanism of resistance to diseases and pests. Moreover, this behaviour trait can be improved through selective breeding (14)(15)(16)(17). Assessed in this way, colony-level hygienic behaviour has high heritability, such as h 2 = 0.63 and 0.65 (13).…”
Section: Introductionmentioning
confidence: 99%
“…From cells of brood we calculated the number of cells sealed by applying the multiplier of 0.53 derived by Delaplane (1999). From mites on adult bees and mites in brood we could derive ending mite populations and percentage of mite population in brooda positive indicator of the fecundity of a mite population (Harbo and Harris, 1999 (Harbo, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, active defense mechanisms such as grooming and hygienic behavior have been most commonly investigated (e.g., Boecking, 1992;Boecking & Spivak, 1999;Harbo & Harris, 1999;Harbo & Hoopingarner, 1997;Peng, Fang, Xu, & Ge, 1987). In grooming behavior, honey bee workers try to get rid of mites, either by grooming themselves or other nestmates.…”
Section: Introductionmentioning
confidence: 99%